1989
DOI: 10.1007/bf01646881
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an occlusive zinc medicated dressing on the bacterial flora in excised wounds in the rat

Abstract: The effects of three different dressings - two occlusive and one non-occlusive - on the bacterial flora of excised wounds in rats were studied. The number of colony forming units per gram of granulation tissue were significantly lower 4, 8 and 12 days postoperatively in wounds treated with a zinc medicated occlusive dressing compared with wounds treated with non-zinc medicated occlusive hydrocolloid dressing or wet-to-dry non-occlusive gauze dressing. The minimum inhibitory concentration (MIC) of zinc sulphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…For example, minimum inhibitory concentrations (MICs) of Zn 21 on aerobic bacteria isolated from human wound infections were determined in one study. 173 Four susceptibility grades emerged from the study: Similar sensitivity patterns were observed for clinical isolates from burn wounds. 174 Zinc oxide also showed antibacterial activity against aerobic and anaerobic endodontal pathogens.…”
Section: Zinc Is An Antimicrobial and Anti-inflammatory Agentmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, minimum inhibitory concentrations (MICs) of Zn 21 on aerobic bacteria isolated from human wound infections were determined in one study. 173 Four susceptibility grades emerged from the study: Similar sensitivity patterns were observed for clinical isolates from burn wounds. 174 Zinc oxide also showed antibacterial activity against aerobic and anaerobic endodontal pathogens.…”
Section: Zinc Is An Antimicrobial and Anti-inflammatory Agentmentioning
confidence: 65%
“…Gram‐positive organisms appear to be more sensitive to zinc than Gram‐negative bacteria. For example, minimum inhibitory concentrations (MICs) of Zn 2+ on aerobic bacteria isolated from human wound infections were determined in one study 173 . Four susceptibility grades emerged from the study:…”
Section: Clinical Validation Of Zinc In Wound Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical zinc oxide has also demonstrated significant antibacterial and antiinflammatory properties. In a rat model, occlusive zinc dressings inhibited growth of Gram‐positive organisms, including Staphylococcus aureus and Streptococcus groups A, B, C, and G 19 . Burn wounds in human patients treated with topical zinc have also demonstrated less growth of S. aureus 20 .…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Soderberg et al obtained minimum inhibitory concentration data for human wound infection-derived bacteria that were exposed to Zn +2 . 23 Different susceptibility rates were noted for Enterococcus sp., Proteus sp., Pseudomonas aeruginosa, (MICs of 8-32 mmol/L); Enterobacter sp., Escherichia coli, Klebsiella sp. (MICs of 4-8 mmol/L); Staphylococcus aureus, Streptococcus group B (MICs of 2-4 mmol/L); and Streptococcus groups A, C, and G (MICs of 0.5-2 mmol/L).…”
mentioning
confidence: 98%